2020
DOI: 10.1111/nph.17099
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell analysis clarifies mosaic color development in purple hydrangea sepal

Abstract: Summary Hydrangea sepals exhibit a wide range of colors, from red, through purple, to blue; the purple color is a color mosaic. However, all of these colors are derived from the same components: simple anthocyanins, 3‐O‐glycosyldelphinidins, three co‐pigment components, acylquinic acids and aluminum ions (Al3+). We show the color mosaic is a result of graded differences in intravacuolar factors. In order to clarify the mechanisms of mosaic color, we performed single‐cell analyses of vacuolar pH, and anthocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…7 ). 40 , 41 ) Interestingly, using this method, we reported that the molar equivalent of 5- O -acylquinic acids ( 2 , 3 ) to anthocyanins ( 1 , 5 ) was strongly correlated with blue cell coloration; however, the content of anthocyanin and 3- O -caffeoylquinic acid ( 4 ) did not correlate with cell color. Nonetheless, these results indicated a clear contribution of 5- O -acylquinic acids ( 2 , 3 ) to the blue sepal cell color in hydrangea.…”
Section: Single-cell Analysis For the Clarification Of Mosaic Purple mentioning
confidence: 99%
See 4 more Smart Citations
“…7 ). 40 , 41 ) Interestingly, using this method, we reported that the molar equivalent of 5- O -acylquinic acids ( 2 , 3 ) to anthocyanins ( 1 , 5 ) was strongly correlated with blue cell coloration; however, the content of anthocyanin and 3- O -caffeoylquinic acid ( 4 ) did not correlate with cell color. Nonetheless, these results indicated a clear contribution of 5- O -acylquinic acids ( 2 , 3 ) to the blue sepal cell color in hydrangea.…”
Section: Single-cell Analysis For the Clarification Of Mosaic Purple mentioning
confidence: 99%
“…Nonetheless, these results indicated a clear contribution of 5- O -acylquinic acids ( 2 , 3 ) to the blue sepal cell color in hydrangea. 40 , 41 )…”
Section: Single-cell Analysis For the Clarification Of Mosaic Purple mentioning
confidence: 99%
See 3 more Smart Citations